Wireless Broadband Access: Policy Implications of Heterogeneous Networks - Juan Rendon Schneir (International Telecommunications Society (ITS), 2010)
A wireless heterogeneous network can help increase the access transmission speed and contribute thereby to the broadband deployment policies of administrations and telecommunications operators. Given the technical particularities of wireless heterogeneous networks, the deployment of wireless heterogeneous networks raises a number of challenges that need to be addressed by regulatory authorities. This article analyses the following regulatory implications: standardisation and technology neutrality, spectrum management, market analysis, open access and infrastructure sharing, interconnection pricing and charging, broadband deployment policies, and privacy and security issues.
Keywords: 330; 4G; heterogeneous networks; cooperative networks; spectrum management; regulation; wireless networks